Sex Differences in Long-Term Quality of Life Among Survivors After Stroke in the INSTRUCT. Issue 9 (September 2019) - Phan, Hoang T.; Blizzard, Christopher L.; Reeves, Mathew J.; Thrift, Amanda G.; Cadilhac, Dominique A.; Sturm, Jonathan; Heeley, Emma; Otahal, Petr; Rothwell, Peter; Anderson, Craig S.; Parmar, Priya; Krishnamurthi, Rita; et al.
Abstract : Background and Purpose—: Women are reported to have poorer health-related quality of life (HRQoL) after stroke than men, but the underlying reasons are uncertain. We investigated factors contributing to the sex differences. Methods—: Individual participant data on 4288 first-ever strokes (1996–2013) were obtained from 4 high-quality population-based incidence studies from Australasia and Europe. HRQoL utility scores among survivors after stroke (range from negative scores=worse than death to 1=perfect health) were calculated from 3 scales including European Quality of Life-5 Dimensions, Short-Form 6-Dimension, and Assessment of Quality of Life at 1 year (3 studies; n=1210) and 5 years (3 studies; n=1057). Quantile regression was used to estimate the median differences in HRQoL for women compared to men with adjustment for covariates. Study factors included sociodemographics, prestroke dependency, stroke-related factors (eg, stroke severity), comorbidities, and poststroke depression. Study-specific median differences were combined into pooled estimates using random-effect meta-analysis. Results—: Women had lower pooled HRQoL than men (median differenceunadjusted 1 year, −0.147; 95% CI, −0.258 to −0.036; 5 years, −0.090; 95% CI, −0.119 to −0.062). After adjustment for age, stroke severity, prestroke dependency, and depression, these pooled median differences were attenuated, more greatly at 1 year (−0.067; 95% CI, −0.111 to −0.022) than at 5 years (−0.085; 95% CI, −0.135 to −0.034). Conclusions—: Women consistently exhibited poorer HRQoL after stroke than men. This was partly attributable to women's advanced age, more severe strokes, prestroke dependency, and poststroke depression, suggesting targets to reduce the differences. There was some evidence of residual differences in HRQoL between sexes but they were small and unlikely to be clinically significant. Abstract : Supplemental Digital Content is available in the text.